Optimalisasi Keterlibatan Audiens Pada Organisasi Nirlaba Pedesaan: Studi Kasus Strategi Media Sosial Yayasan Odesa Indonesia - Rayhan Muhammad Yasin; Iis Kurnia Nurhayari (Fakultas Seni Rupa dan Desain ITB, 2026)
The growing reliance on social media as a central communication infrastructure has required nonprofit organizations to adopt more deliberate and adaptive digital strategies to sustain audience engagement. This study examines the digital communication strategy of the Odesa Foundation, focusing on content management practices and audience interaction across Instagram, YouTube, Facebook, and TikTok. Employing a qualitative case study design, the research draws on in-depth interviews with key organizational actors, systematic observation of social media activity over a specified period, and analysis of documented content using engagement indicators such as likes, comments, shares, and interaction patterns. The findings reveal that, despite consistent platform utilization, audience engagement remains limited due to low interactivity in content, misalignment with platform-specific audience preferences, and inconsistent posting frequency. The study contributes to the development of context-sensitive digital communication frameworks for rural nonprofit organizations by demonstrating how structural constraints and strategic choices shape engagement outcomes. Practical implications highlight the importance of platform-responsive content design, the integration of interactive features, and the use of data-driven evaluation to improve communication effectiveness. The analysis is constrained by its single-case scope, which may limit broader generalization, yet it provides a grounded basis for future comparative research on nonprofit digital communication strategies.